2005
DOI: 10.1634/stemcells.2005-0079
|View full text |Cite
|
Sign up to set email alerts
|

Human Cord Blood–Derived Cells Generate Insulin‐Producing Cells In Vivo

Abstract: Here we report the capacity of human cord blood (CB) -derived cells to generate insulin-producing cells. To investigate in vivo capacity of human CB-derived cells, T celldepleted mononuclear cells were intravenously transplanted into nonobese diabetic/severe combined immunodeficient/β 2 -microglobulin null mice within 48 hours of birth. At 1-2 months post-transplantation, immunofluorescence staining for insulin and fluorescence in situ hybridization (FISH) analysis using a human chromosome probe indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 46 publications
0
34
0
Order By: Relevance
“…Umbilical cord blood (UCB) is a fairly good source of pluripotent MSCs and HSCs with lineage specificity 2 and hence is rapidly gaining attention for its proposed therapeutic values. 3,4 The UCB derived MSCs also exhibit the potential to differentiate into the insulin producing beta cells [5][6][7][8] and hence can be used as an alternative for pancreatic progenitor cells. However the availability of cord blood will be limited in due course of time, as most of the cord blood would be cryopreserved for banking purposes; hence there is a dire need to look for an alternative source of stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…Umbilical cord blood (UCB) is a fairly good source of pluripotent MSCs and HSCs with lineage specificity 2 and hence is rapidly gaining attention for its proposed therapeutic values. 3,4 The UCB derived MSCs also exhibit the potential to differentiate into the insulin producing beta cells [5][6][7][8] and hence can be used as an alternative for pancreatic progenitor cells. However the availability of cord blood will be limited in due course of time, as most of the cord blood would be cryopreserved for banking purposes; hence there is a dire need to look for an alternative source of stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…At present, hUC-MSCs appear to be a promising and safe cell source for transplantation due to their high potential for proliferation, multipotential differentiation and a low level of immunogenicity. According to the diabetic rats' models by Wang et al, hyperglycemia of the diabetic rats was corrected and the damage of pancreatic cells was partly repaired in the hUC-MSCs transplantation groups [29][30][31] .…”
Section: Prospect Of Diabetes Therapymentioning
confidence: 99%
“…Another study showed that the insulin-producing cells differentiated from UCB-derived MSCs with extracellular matrix gel secreted insulin but are not responsive to glucose (22). Furthermore, Yoshida et al proved the regenerative property and the differentiation of UCB-derived cells to insulin-producing cells (23). When they transplanted UCB stem cells into immune deficient NOD/scid mice by intravenous injection, they could detect human UCB-derived insulin-positive cells in the pancreas of the recipient.…”
Section: Umbilical Cord Blood Stem Cellsmentioning
confidence: 99%